Calculation of the robot trajectory for the optimum directional orientation of fibre placement in the manufacture of composite profile frames. (October 2015) - Martinec, Tomáš; Mlýnek, Jaroslav; Petrů, Michal
Abstract: This article deals with theissue of calculating the trajectory of the end-effector of an industrial robot in the manufacture of composites. In the introduction to the article we describe the basic approaches used in the manufacture of composites. Robots are used to define the winding orientation of carbon fibre strands on an uneven polyurethane 3D core. The core is attached to the robot-end-effector and is led through a fibre-processing head according to a suitably defined robot trajectory during dry carbon fibre winding on the core. The model of a passage of the polyurethane core through a fibre-processing head is described in the article. The placement of the fibre-processing head is defined in the basic Euclidean coordinate system E3 of the robot. The core is specified in the local coordinates of the Euclidean coordinate system E3, the origin of this local system is in the robot-end-effector. The positioning of the local system in the basic system of the robot is entered using the "tool centre point" of the robot. A matrix calculus is used when calculating the trajectory robot-end-effector to determine the desired passage of the core through the fibre-processing head. Gradually, the required rotation and translation matrices of the local coordinate system of the robot-end-effector relative to the basic system are calculated and subsequently the Euler angles of rotation are determined corresponding to the transformation matrices. This is used to determine the sequence of values of the "tool centre point" for defining the desired trajectory of the robot-end-effector. The calculation for the trajectory was programmed in the Delphi development environment. The article also solves practical tasks of the polyurethane core passage through the fibre-processing head. The calculations of the trajectory of the robot-end-effector were used as input values for the graphic software simulator and at the same time winding of carbon strands on the polyurethane core was verified for the calculated trajectory of the robot-end-effector in the experimental laboratory. Highlights: The described algorithm allows us to calculate and determine the accurate 3D trajectory of the end-effector of an industrial robot during the manufacture of composite profiles using a dry fibre winding technology on a polyurethane core with a circular cross-section. The algorithm can be applied to any manufacturing process where it is necessary to determine the 3D trajectory of a robot end-effector. Suppliers of industrial robots currently offer specific software tools facilitating control of the robot end-effector when programming specific tasks (machining, welding, cutting, grinding or painting) but none of them are suitable for use for the described task. In engineering and manufacturing practice, there are specific activities that require the determination of an industrial robot trajectory but it often occurs that a suitable commercial software product does not exist or is not available for the technician. The algorithm allows us to determine the exact trajectory of the robot end-effector, which provides a significant advantage over manually entered robot trajectory. It requires practical experience of technician and this technique is time-consuming. Use of the described algorithm is completely independent of the type of production robot and software tools. Possibility to accurately determine the desired trajectory of the robot end-effector using the algorithm can be beneficial for optimizing the robot trajectory in the production cycle. The procedure for determining the trajectory of the robot end-effector is at virtually no additional cost to the manufacturer and can significantly speed up the determination of the desired trajectory of the end-effector. The described algorithm in article can be successfully utilized by the technicians of manufacturing robotic workplaces and also by developers of specific software tools for controlling of manufacture robots.